(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Many properties of nuclear structure for even-even isotopes have been investigated with and .They examined carefully with benefit from continuously updating of nuclear decay schemes. Low-lying energy levels for even-even positive parity states, mixed symmetry states (MSS), reduced electric quadruple transitions probabilities , branching ratios, reduced magnetic dipole transitions probability , ratio, reduced electric monopole transitions probability and mixing ratio and potential energy surface have been studied. In the framework of noted the competition between the two parameters ( and ) in 124-128Ba isotopes were the increases of a0 associated with decreases of a2 which mean that the γ-unstable features were continuous increases with opposite of rotational properties , in IBM-2 χπ and χν were (-1.3 and around 0.7) which signified similarity with IBM-1 expected. 124-128Ba isotopes described to be transitional nuclei , transitional between SU(3) and O(6) features.